EXPERIMENTAL VALIDATION OF A CAPPILARY TUBE SIMULATION MODEL WITH REFRIGERANT MIXTURES FLOW - Fiorelli, F. A. S.; Silvares, O. M. (Revista de Engenharia Térmica, 2004)
This paper presents the experimental validation of a simulation model for refrigerant mixtures flow through capillary tubes. To perform such validation it was built an experimental apparatus using a blow-down process. It was carried out preliminary tests for characterization of experimental parameters: actual capillary tube diameters; relative roughness; and the heat losses in subcooling/quality control system. It was obtained almost 200 experimental points for R-407C (a zeotropic mixture) and R-410A (a near azeotropic mixture). Complete data set for each point consists of the measured pressure and temperature profiles, mass flow rate and mixture composition, as well as subcooling/quality control system inlet and outlet temperatures and heater electric power consumption for tests with two-phase flow capillary tube inlet conditions. Comparison of simulation and experimental data show a good agreement. Main deviations are connected with the delay of vaporization phenomenon occurrence, experimentally verified by the authors.